The reality of using smart devices to develop the linguistic abilities of older first-year students - Al-Juhani, Mona Mabrouk Moawad; Al-Dosari, Mashael Saleh (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to investigate the use of smart devices in developing linguistic competencies among first-grade female students. To achieve this goal, a descriptive approach was used, along with a questionnaire consisting of five dimensions and 27 items. It was distributed to a simple random sample of (81) elementary school first-grade teachers in Madinah in 1445 AH, The study yielded several key results, including the following: - The first dimension, "Using smart devices by first-grade students to develop grammatical proficiency," had an average score of 3.95 and a standard deviation of 86, indicating a high use of smart devices for developing grammatical proficiency according to teachers' perspectives - The second dimension, "Using smart devices by first-grade students to develop speech proficiency," had an average score of 3.81 , showing a high use of smart devices for developing speech proficiency according to teachers' perspectives. The third dimension, "Using smart devices by first-grade students to develop social linguistic competencies," had an average score of 4.02, indicating a high use of smart devices for developing social linguistic competencies according to teachers' perspectives. The fourth dimension, "Using smart devices by first-grade students to develop linguistic competencies," had an average score of 4.06, showing a high use of smart devices for developing linguistic competencies according to teachers' perspectives. Finally, the fifth dimension, "Difficulties faced by first-grade students in acquiring linguistic competencies in light of using smart devices," had an average score of 3.91 , indicating a high level of difficulty in using smart devices for developing linguistic competencies. Based on these results, the study made several recommendations, including utilizing smart devices to enhance grammatical rules, promoting their use in syntax, encouraging students to use smart devices to improve their speaking skills, and urging students to use smart devices to creatively present their experiences in the surrounding environment.
Keywords: Reality; Smart Devices; Development; Linguistic Competencies